Analysis Effect of Human Development Index (HDI), Regency/City Minimum Wage (UMK), Investment and Unemployment Rate on the Number of Poor People in Bali Province in 2012-2021 - Apriyanti Kusuma Dewi; Siti Fatimah Nurhayati (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2023)
This study aims to analyze the effect of the human development index (HDI), regency/city minimum wage (UMK), investment and unemployment rate on the number of poor people in Bali Province in 2012-2021. The analysis tool used is panel data regression. Panel data is a combination of time series and cross sections. Research data in the form of secondary data includes the human development index(HDI), regency/city minimum wage(UMK), investment, unemployment rate and the number of poor people obtained from the Central Statistics Agency (BPS). The results showed that the best model chosen was the fixed effect model (FEM). Based on the analysis of the FEM model, it shows that the human development index, the regency/city minimum wage affects the number of poor people in Bali province in 2012-2021. Meanwhile, investment variables and unemployment rate do not affect the number of poor people in Bali province. The coefficient of determination 0,9429 means that 94,29% of the variable variation in the number of poor people in Bali province can be explained by the variables of human development index (HDI), regency/city minimum wage (UMK), investment and unemployment rate. The remaining 5,71% is explained by other free variables that are not included in the model.